Matte separated behavior from slag during the cleaning process by using waste cooking oil as carbon neutral reductant - Shiwei Zhou; Linchuan Wang; Yonggang Wei; Bo Li; Hua Wang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
As a sustainable biomass resource, waste cooking oil (WCO) has not been widely used. Based on the cracking characteristics of WCO at high temperature, using WCO as a reductant to reduce the copper slag for cleaning was proposed. A series of laboratory-scale copper slag cleaning experiment was carried out. The matte separated behavior from slag during the reduction and sedimentation stage of copper slag cleaning by using WCO was studied in detail. The results indicate that the reduction of Fe3O4 mainly occurred in the injection stage, and majority of the matte particles were precipitated and separated. In the sedimentation stage, the content of Fe3O4 in the slag is low (< 3.5wt.%), which enhances the fluidity of the slag and makes the small matte particles finally sedimentation to the matte layer. The content of copper in the middle and upper slag is reduced to less than 0.57 wt.%, and the green cleaning of copper slag is realized.